Estágio supervisionado obrigatório relato de caso: rinotraqueíte viral felina ( Herpes vírus felino tipo-1) em filhotes de gatos doméstico (Felis catus) - Nogueira, Rebeca Milfont (Universidade Federal Rural do Semi-Árido, 2018)
The Mandatory Supervised Internship is of extreme importance for the training of students of the veterinary medicine course. Whereas it contributes significantly to the introduction of professionals into the labor market. In this way, the purpose of this report is to describe the activities carried out in the compulsory supervised traineeship, whose objective was to improve the knowledge acquired during the undergraduate course in veterinary medicine. The stage was carried out at the veterinary hospital of the Federal Rural Semi-Arid Federal University (HOVET-UFERSA), Mossoró-RN, from December 6, 2017 to March 6, 2018, for 240 hours. The description of three kittens with Feline viral rhinotracheitis was chosen as the case being reported. The three undefined (orphan) puppies, about one month old. These animals were rescued from a shelter and arrived with a history of nasal discharge, sneezing, fever and lack of appetite. Physical examination revealed malnutrition, dehydration, apathy, hyperthermia, pale mucous membranes, presence of mucopurulent nasal discharge and bilateral keratitis. According to clinical signs presumptive diagnosis of feline viral rhinotracheitis. Treatment with penicillin G benzanthine, G potassic, procaine G and dihydrostrepromician G was instituted for 7 days, every 24 hours. In addition, the ocular and nasal secretions were cleansed, and dexametason 1mg\ml and fluibuprofen eye drops were applied. every 12/12 hours, in addition to nebulization with physiological solution NaCl a 0,9 %, supplementation with hypercaloric concentrate and fluid therapy. The patients presented gradual improvement. In view of this it can be concluded that ESOIII is a valuable step for ethical and professional maturation in the training of a veterinarian, and that rhinotracheitis is a morbid condition that must be identified and when appropriate therapy is prescribed the animals recover.
Relatório
Keywords: Afecção respiratória; Felinos; Espirros; Gatos; Respiratory condition; Felines; Sneezing; Cats; CIENCIAS AGRARIAS::MEDICINA VETERINARIA